Sistem Pendukung Keputusan Pemilihan Bimbingan Belajar Terbaik Kota Pekalongan Menggunakan Metode Promethee - Lami, M Dhiyaul; Pramuntadi, Andri; Prastowo, Wahit Desta; Gutama, Deden Hardan (Jurnal Teknik Industri Terintegrasi (JUTIN), 2024)
Tutoring institutions for elementary school levels have been proliferating in Pekalongan City due to the large number of elementary school students, totaling 18,356 students spread across 103 schools. Finding the right tutoring center that meets specific needs can sometimes be challenging. This study aims to assist with this by developing a decision support system. Using the Promethee method, which offers a more detailed evaluation of multiple criteria, the system is expected to provide a suitable decision support solution. This research produces a web-based decision support system that parents can use to find a tutoring center that meets their desired criteria.